Pemikiran Pendidikan Imam Al-Ghazali: Integrasi Ilmu, Akhlak, dan Spiritualitas - Rocyayah, Anita; Abdullah Khoir, Mulyanto; Fuad, Anisul; Pitriatin (Jurnal Penelitian Tarbawi: Pendidikan Islam dan Isu-Isu Sosial, 2026)
Imam Al-Ghazali’s educational thought constitutes a fundamental contribution to the development of Islamic education, emphasizing the integration of intellectual, moral, and spiritual dimensions. This article aims to examine comprehensively Al-Ghazali’s concept of education, including his biographical background and intellectual journey, the core principles of his educational thought, its distinctive characteristics, his contributions to Islamic educational discourse, and the relevance of his ideas in addressing contemporary educational challenges. This study employs a qualitative approach using library research by analyzing Al-Ghazali’s major works, such as Iḥyā’ ‘Ulūm ad-Dīn, Ayyuha al-Walad, Bidayat al-Hidayah, and al-Munqidz min ad-Dalal, along with supporting scholarly literature. The findings reveal that Al-Ghazali conceives education as a process of tazkiyat al-nafs (purification of the soul) and moral formation oriented toward attaining closeness to Allah (SWT), rather than merely transferring knowledge. The distinctiveness of his educational thought lies in its holistic approach, which integrates knowledge, action, and morality, and positions educators as moral and spiritual role models. In the context of modern education, which tends to prioritize cognitive achievement and academic competition, Al-Ghazali’s educational philosophy remains highly relevant as an ethical and philosophical foundation for strengthening character education and students’ spiritual development. This study affirms that Al-Ghazali’s educational thought possesses not only historical significance but also practical and conceptual value for the development of a humanistic, value-oriented, and spiritually grounded Islamic education Keywords: Imam Al-Ghazali, Islamic education, morality, tazkiyat al-nafs, character education.